Monetary policy and stock market boom-bust cycles - Lawrence Christiano; Cosmin Ilut; Roberto Motto; Massimo Rostagno (European Central Bank (ECB), 2008)
We explore the dynamic effects of news about a future technology improvement which turns out ex post to be overoptimistic. We find that it is difficult to generate a boom-bust cycle (a period in which stock prices, consumption, investment and employment all rise and then crash) in response to such a news shock, in a standard real business cycle model. However, a monetized version of the model which stresses sticky wages and a Taylorrule based monetary policy naturally generates a welfare-reducing boom-bust cycle in response to a news shock. We explore the possibility that integrating credit growth into monetary policy may result in improved performance. We discuss the robustness of our analysis to alternative specifications of the labor market, in which wage-setting frictions do not distort on going firm/worker relations.
Keywords: C11; C51; E5; E13; E32; 330; Asset price boom-busts; DSGE Models; monetary policy; Geldpolitik; Börsenkurs; Finanzkrise; Real-Business-Cycle-Theorie; Taylor-Regel; Kreditmarkt; Arbeitsmarkt; Dynamisches Gleichgewicht; Theorie